THE PROBLEM OF DETERMINING THE RELIABILITY OF THE IMAGE OF AMIR TEMUR IN THE ASPECT OF HISTORICAL LEGENDS - RAKHMONOVA MAKHBUBA RAVSHANOVNA (Western European Studies, 2024)
The problem of determining the degree of historical authenticity of the image of Amir Temur in the aspect of historical legends about him is considered using the example of Christopher Marlowe’s drama “Tamerlane the Great”. Based on a number of different sources, the author comes to the conclusion that K. Marlowe does not set out to adhere to historical truth, since the main ideological content of the drama is addressed to current socio-political and social problems of contemporary reality
Keywords: poetics; historical genre; historical legends; fiction